Brand, Price, and Word of Mouth Impact Global Consumer Choices: Pengaruh Merek, Harga, dan Promosi dari Mulut ke Mulut terhadap Pilihan Konsumen Global - Achmad Riski Kurniawan; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the influence of brand image, price, and Electronic Word of Mouth (E-WOM) on purchasing decisions in the e-commerce platform, Shopee. Using a quantitative approach, data from 96 respondents in Sidoarjo Regency were analyzed through Smart-PLS Version 3.0. Results reveal significant effects of brand image, price, and E-WOM on purchasing decisions, with brand image reflecting reputation, effectiveness, and trustworthiness, while price considerations include affordability, quality alignment, competitiveness, and benefit congruence. E-WOM's impact is seen through intensity, content, and valence of opinion. These findings highlight the importance of these factors in influencing consumer behavior on Shopee. However, the study's focus on these three variables suggests a need for future research to explore additional factors impacting e-commerce purchasing decisions, contributing to a deeper understanding of consumer behavior in online retail settings. Highlights: Consumer Behavior: Brand image, price, and E-WOM influence Shopee purchasing decisions. Data Analysis: Smart-PLS analyzes 96 respondents' data on e-commerce behavior. Research Implications: Further exploration needed for comprehensive understanding of online consumer behavior. Keywords: e-commerce, Shopee, purchasing decisions, brand image, Electronic Word of Mouth (E-WOM)